Characteristics and outcomes of patients with formiminoglutamic aciduria detected through newborn screening. Issue 1 (11th February 2019) - Ahrens‐Nicklas, Rebecca C.; Ganetzky, Rebecca D.; Rush, Peggy W.; Conway, Robert L.; Ficicioglu, Can
Abstract: Background: Glutamate formiminotransferase deficiency (FTCD deficiency) or formiminoglutamic aciduria is the second most common of the known inherited disorders of folate metabolism. Initial case reports suggested that patients may have severe intellectual disability and megaloblastic anemia. However, these cases were obtained from screening cohorts of patients with developmental delay. Subsequently, patients with milder clinical phenotypes have been reported. The full phenotypic spectrum of this disorder remains unknown. Methods: In many states, FTCD deficiency can be incidentally detected on tandem mass spectrometry‐based newborn screening of dried blood spots. In this work, we report the outcomes of infants identified to have FTCD deficiency through newborn screening. Results: During the study period, 18 patients were identified to have FTCD deficiency and were referred and evaluated at one of the two participating metabolic centers. The overall rate of FTCD deficiency detected through the New Jersey screening program over the study time period was 1:58, 982. At a mean age of 56 months at last follow‐up: 3/18 (16%) had developmental delays requiring individualized education plans, no patients had profound intellectual disability; 4/16 (25%) had mild self‐limited anemia, no patients had profound anemia. Conclusions: These data suggest that the majority of individuals with FTCD deficiency detected by newborn screening are asymptomatic.